Ownership structure and the risk-taking channel of monetary policy - Caselli, Giorgio (Cranfield University, 2017)
Recent years have seen a growing interest in the implications of monetary policy for bank risk taking and financial stability. Yet, there has hitherto been limited attention on how ownership structure affects the relationship between monetary policy and bank risk. Drawing on three interconnected studies written as journal articles, this thesis provides novel insights into the role of banks in monetary policy transmission. First, it refines our understanding of the monetary transmission process via financial intermediaries. Based on a systematic review of 152 articles published during the 1963–2016 period, this research integrates a highly fragmented body of evidence into a multidimensional framework that combines the mechanisms of monetary transmission through financial institutions with the conditions underpinning the functioning of each mechanism. Second, this thesis incorporates concepts from the property rights and agency theory perspectives into the analysis of the risktaking channel. By building a sample of commercial, cooperative and savings banks from 17 Western European countries over the 1999–2011 period, this study finds that the impact of lower interest rates on bank risk taking is reduced for stakeholder banks relative to their shareholder counterparts. Third, this research contributes to the current debate about how to design a more stable and resilient financial system by introducing diversity measures from ecological theories into the study of the monetary policy–bank risk nexus. After estimating the ownership composition of the banking sector in terms of relative market shares of shareholder banks vis-`a-vis stakeholder banks, this work shows that the effects of unexpected monetary policy shocks on banks’ probability of default is dampened in countries with greater ownership diversity. Taken together, these findings advance knowledge in this field of enquiry by highlighting the need to account for differences in ownership structures when assessing the implications of the monetary environment for bank riskiness.
Keywords: Bank risk taking; financial crisis; financial stability; monetary transmission mechanism; ownership diversity; systematic literature review